STATISTICAL STUDY OF ENSURING THE FINANCIAL STABILITY OF ENTERPRISES IN THE NEW UZBEKISTAN - Жураев Хуршид Маматкулович (Web of Journals Publishing, 2025)
This article examines the necessity, essence and factors, goals, objectives and problems of managing the financial stability of an enterprise at the current stage of liberalization and modernization of the economy of the Republic. The advantages and specific features of a creative approach to effective measures for managing the financial stability of an enterprise in the prospects of the country's socio-economic development are scientifically substantiated.
Keywords: Corporate finance, corporate financial management, financial stability, management of the financial stability of an enterprise, assessment of the financial stability of an enterprise, level of financial stability of an enterprise, indicators of the level of financial stability of an enterprise and their assessment methodology.